Communities of Absence: Emotions, Time, and Buddhism in the Creation of Belonging - Baffelli, Erica (Numen, 2021)
Abstract This article argues that belonging can be characterized by absence. It explores this as experienced in two different geographical and historical contexts by two groups of actors: members of the early Tibetan diaspora in India (1959–1979) and former members of a religious group (Aum Shinrikyō) in Japan. The absence we conceptualize is double: it is not solely a spatial absence, but also a temporal absence in terms of the irreversibility of time. It is felt and articulated through emotions that play decisive roles in the constitution and sustaining of these communities. These communities as feeling communities are characterized by absence, but absence is simultaneously what makes them a community. This simultaneity allows our actors to create complex temporal frameworks by relating to reimagined pasts, different presents, and potential futures. Therefore, the article contributes to discussions of belonging by retheorizing the relationship between absence, emotions, and time.